2008
DOI: 10.1007/s00213-008-1085-z
|View full text |Cite
|
Sign up to set email alerts
|

Abuse potential of carbohydrates for overweight carbohydrate cravers

Abstract: Rationale-The long-rejected construct of food addiction is undergoing re-examination. Objectives-.To evaluate whether a novel carbohydrate food shows abuse potential for rigorously defined carbohydrate cravers, as evidenced by selective self-administration and mood enhancement during double-blind discrimination testing.Methods-Discrete trials choice testing was performed with 61 overweight (BMI m=27.64, SD=2.59) women (ages 18-45; 19.70% African American) whose diet records showed >4 weekly afternoon/evening e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 55 publications
0
44
0
1
Order By: Relevance
“…These experiments [e.g. [70], however, do not overcome methodological flaws and do not point toward a systemic rewarding effect of specific carbohydrates. …”
Section: Obesitymentioning
confidence: 99%
“…These experiments [e.g. [70], however, do not overcome methodological flaws and do not point toward a systemic rewarding effect of specific carbohydrates. …”
Section: Obesitymentioning
confidence: 99%
“…Primary reinforcers such as tobacco, other substances, and even appealing foods trigger the brain's reward circuitry quite directly, enabling contextual cues to ingrain behavioral habits that become very challenging to change. [49][50][51] The person who is trying not to smoke or overeat faces an ambivalent choice between responding to an immediately available, potent reward versus delaying gratification to stave off long-term adverse health consequences. 52 Social cognitive theory, the dominant contemporary theory of health behavior, credits people with having cognitive and social resources to cope with such challenges.…”
Section: Behavioral Sciencesmentioning
confidence: 99%
“…A number of studies address issues related to the excessive intake of sweets and the possible association to abuse and dependence (Avena, Rada, & Hoebel, 2008;Kampov-Polevoy et al, 2006). Some authors have reported evidence of comorbidity between substance abuse and excessive desire ("craving") or preference for solutions with high concentrations of sucrose (Avena et al, 2008;Janowsky, Pucilowski, & Buyinza, 2003;Kampov-Polevoy et al, 2006;Pelchat, 2002;Spring et al, 2008). Tobacco studies have shown that sugar may attenuate tobacco craving and withdrawal symptoms (Berlin, Vorspan, Warot, Maneglier, & SpreuxVaroquaux, 2005).…”
Section: Sugar Dependence Constructmentioning
confidence: 99%